PENTINGNYA FAMILIARITAS: STUDI MENGENAI BAGAIMANA MULTITASKING DAPAT DILAKUKAN DAN DIPELAJARI - , Wisnu Wiradhany, Dr. Neila Ramdhani, M.Si., M.Ed. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Cognitive Load Theory (CLT) explained how familiar task is easier to finish for its low utilization of short-term memory. This study aims to discover the role of task familiarity in multitasking: why novel task is harder to multitask with other, and whether if multitasking can be trained or learned by high exposure to multitasking condition. Using quasi-experimental design with reading comprehension skill as benchmark, the results show that subjects doing familiar task showed better reading comprehension skill (F (1,86) =10.317